Penerapan Kartu Stok pada Persediaan Produk Minuman Fungsional di P4S X Kabupaten Kulon Progo - Arini Dara Pitasari; Siwitri Munambar; Geraldo Adinugra Rimartin (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the application of stock card systems in inventory management among micro, small, and medium enterprises (MSMEs), despite their significant potential to enhance stock control effectiveness and operational sustainability, particularly in the herbal beverage sector. The purpose of this study is to explore the implementation and evaluate the effectiveness of stock card usage for recording functional beverage inventory, with a focus on the Telang Sari business unit at P4S X, Kulon Progo Regency. Employing a qualitative case study approach, the research involved a single business unit selected through purposive sampling. Data were collected through semi-structured interviews, direct observation, and visual documentation, and analyzed thematically. The findings indicate that the use of stock cards improves record accuracy, accelerates stock-checking processes, and fosters a more disciplined work culture in warehouse management. These results support Grindle’s contextual-based management approach and demonstrate that simple yet systematic manual recording systems can serve as effective solutions for non-digitized MSMEs. The implications of this study include theoretical contributions to the literature on manual inventory control and practical recommendations for MSME actors and support institutions to adopt stock cards as an initial step toward a more integrated inventory management system. This study also opens pathways for further research on the integration of manual and digital systems in the microenterprise sector.